A Novel Oscillation Criterion for Fourth-Order Differential Equations - Al-Suwaidi, Amira Fadhil; Antonelli, Sophia; Bonfiglioli, Alessandro (Journal of Computer Engineering, 2024)
The main purpose of this manuscript is to show asymptotic properties of a class of differential equations with variable coefficients 0, where ν ν0 and w (ν) := y (ν) + p (ν) y (σ(ν)). By using integral averaging technique, we get conditions to ensure oscillation of solutions of this equation. The obtained results improve and generalize the earlier ones; finally an example is given to illustrate the criteria